(untitled) (Journal of Educational Sciences, 2024)
In the context of growing competition in higher education, universities in Kazakhstan are increasingly competing for talent not only among students but also among faculty members. However, there is limited understanding of how universities in Kazakhstan are changing their personnel policies in the context of gained autonomy. This article analyzes the systems of academic positions and academic promotion policies as fundamental mechanisms for shaping personnel policies in Kazakhstani universities. Applying document analysis, we analyzed the development strategies, provisions on faculty, and the rating assessment of faculty in two private universities in Kazakhstan. It was found that private universities actively reform their personnel policies in line with their strategic goals and international practices. Career advancement is based on qualifications or the possession of the relevant degree, experience in teaching or practical activities, and research outputs. Although universities in Kazakhstan remain primarily instructional, existing promotion policies, particularly on the teaching track, do not take into account the results of teaching activities. The results of research activities are mainly measured by quantitative indicators that vary between universities. Moreover, evaluation criteria may not be sufficiently clearly defined, creating risks of reducing the level of objectivity and transparency of personnel policies. The results of this study enhance our understanding of the trends in the development of academic advancement policies in developing countries seeking to enter the global academic community of universities. Furthermore, they can be useful for improving the career policies in universities. Keywords: academic career, academic career system, promotion policy, higher education, private university.